Association between body mass index and stroke severity in acute ischaemic stroke with non‐valvular atrial fibrillation. (30th May 2020) - Cho, B‐H.; Cheon, K.; Lee, K‐Y.; Jung, Y. H.; Han, S.W.; Park, J. H.; Choi, H‐Y.; Cho, H‐J.; Park, H. J.; Nam, H. S.; Heo, J. H.; Lee, H. S.; et al.
Abstract : Background and purpose: The objective of this study was to investigate the association between body mass index (BMI) and both initial stroke severity at presentation and functional outcomes after acute ischaemic stroke (AIS) in patients with non‐valvular atrial fibrillation (NVAF). Methods: Patients were categorized on the basis of their BMI into underweight (BMI <18.5, n = 111), normal (18.5 ≤ BMI <25, n = 1036) and overweight to obese (BMI ≥25, n = 472) groups. Initial stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) score and functional outcomes were assessed using the modified Rankin Scale score at discharge. The differences in stroke severity and functional outcomes were compared between groups using robust log‐linear regression with a Poisson distribution and binary logistic regression analysis. Results: A total of 1619 AIS patients with NVAF from six hospitals were included. Compared with the NIHSS scores [median 5, interquartile range (IQR) 2–14] of normal‐weight patients, the NIHSS scores (median 9, IQR 4–19) of underweight patients were more likely to be higher, whereas those of overweight to obese patients were lower (median 4, IQR 1–12) ( P < 0.001). In terms of functional outcomes after stroke, underweight patients had a higher risk of poor functional outcomes (odds ratio 1.78, 95% confidence interval 1.09–2.56, P = 0.01) but overweight to obese patients had no significant difference in functional outcomes compared with normal‐weight patients. Conclusion: An inverse association was found between BMI and stroke severity in AIS patients with NVAF. This suggests the presence of an obesity paradox for short‐term outcomes in patients with NVAF.